Rossette formation in peripheral blood of patients with acute myocardial infarction - L. N. Korichkina; A. V. Solovjeva; Z. Sh. Rogova; L. V. Lavrinenko (Российский кардиологический журнал)
Intravascular auto-rosette formation in peripheral blood of the patients with acute myocardial infarction was investigated. An association between rosette formation rate and necrosis area size was observed. Among individuals with Q-infarction, autorosette formation was by 1,7times more common than in patients with non-Q myocardial infarction. Increase in auto-rosette number was accompanied with decline in red blood cell and hemoglobin levels.